자가 장골 이식술을 이용한 주상골-제 1설상골 간 골연합 환자의 유합술 치료: 증례 보고 - 김성겸; 박재욱; 박현우; Sung-Gyum Kim; Jae-Wook Park; Hyun-Woo Park (대한족부족관절학회지, 2025)
The naviculo-cuneiform coalition is extremely rare and causes chronic midfoot pain and limited mobility. This paper reports a case of a bilateral naviculo-cuneiform coalition in a 23-year-old male patient who presented with persistent midfeet pain unresponsive to conservative treatment. Naviculo-cuneiform arthrodesis using an autologous iliac bone graft was performed on the right foot, followed by the same procedure on the left 1 year later because of symptom progression. Radiographic union was achieved by 12 weeks postoperatively in both feet. The patient reported significant pain relief and returned to normal activities. Arthrodesis using an autologous iliac bone graft may be a useful surgical option for symptomatic naviculo-cuneiform coalition involving a large portion of the joint surface when conservative treatment fails.